Ecotone vegetation and water quality of Rara and Begnas Lakes, Nepal - Lama, Furbe; Thakuri, Sudeep; Ghimire, Narayan Prasad; Malla, Rabin (Himalayan Biodiversity, 2018)
Land-water interfaces of lakes are highly dynamic and are responsible for the stability and maintenance of ecosystems. This study was carried out to understand the ecotone vegetation and the physico-chemical characteristics of waters of Begnas and Rara lakes of Nepal. For vegetation survey, line transects (perpendicular bi-sector to lake boundary), were used along the lake boundaries at an interval of 500 m; three quadrats of 1 m x 1 m size were laid on each line transect (off shore, boundary line, and on shore). All vegetation species in the sample quadrates were recorded. For probing water quality, lakes were divided into three blocks, then sampling was conducted on a consecutive day. Physico-chemical parameters —temperature, pH, electric conductivity (EC), dissolved oxygen (DO), total dissolved solid (TDS), ammonia, and nitrate—were measured. A total of 55 species under 38 families and 28 orders were recorded from ecotone of Begnas lake. In Rara lake, 56 species of 41 families and 22 orders were recorded. Poaceae was the dominant largest family in Begnas which was followed by Asteraceae. In Rara lake, Rosaceae was the dominant family which was followed by Pinaceae. Temperature, pH, and DO values decreased with depth, but EC and TDS e increased with depth, in both Begnas and Rara lakes. Ammonia and Nitrate were below the detectable limit of the instrument, indicating low nutrient contents of both lakes. The study established the baseline information about the diversity of ecotone vegetation; both the lakes show clear changes in physiochemical parameters with lake depths.